Roland Barthes' Semiotic Analysis of the Lyrics of the Song Ḥājah Mistakhbiyah by Muḥammad Ḥamāki (Denotation, Connotation and Myth) - Rustam, Rustam; Ahmad, Muhsin; Pallawagau, Baso (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This article analyzes the lyrics of the song "Ḥājah Mistakhbiyah" by Muḥammad Ḥamāqī using descriptive qualitative methods and a semiotic approach. The aim is to reveal the relationship between signs and reality in the song's lyrics. Research data was obtained from two main sources, namely the song "ḥājah mistakhbiyah" itself and secondary data in the form of books, journals, articles, theses, dissertations which discuss the song "ḥājah mistakhbiyah" and Roland Barthes' semiotics. Analysis of song lyrics is carried out by exploring the semiotic aspects of song lyrics, exploring the semiotic aspects between words by paying attention to the concepts of denotation, connotation and myth. The results of the analysis show that the song "ḥājah mistakhbiyah" has a deep and complex meaning that can be interpreted from various perspectives. Myth analysis shows that this song reflects various myths about human complexity, the strengths and limitations of communication, and the importance of relationships in life. Analysis of denotation and connotation in each song line shows that the meaning of the song does not only lie in the literal meaning of the words, but also in the contextual and emotional meaning.